MEDIA GAMBAR SEBAGAI SARANA MENINGKATKAN KEMAMPUAN MENULIS ATAU WRITING ABILITY BERBAHASA INGGRIS BAGI PARA SISWA YANG BELAJAR BAHASA INGGRIS - Widyahening, Ch Evy Tri (Widya Wacana: Jurnal Ilmiah, 2011)
Abstract Writing ability needs to be mastered by anyone who wishes to communicate with others indirectly. Writing ability is a vital importance for the studentst, the leaders and their employee, teachers and lecturers. The selection of good media for teaching learning process represents one of determinant success in increasing the writing activity. The good media for teaching learning process, for example, is picture. Because by using picture media will arise student imagination in working and pouring their imagination in the Â form of article. Key words : writing ability, pictures media, media for teching learning.